Meaningful Participation in the Formation of Regional Legal Products: An Ideal Model of Local Regulation In the Implementation of Regional Autonomy - Darlis Pattalongi, Muhammad; Vivi Yulianingrum, Aullia; Elviandri, Elviandri (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Meaningful participation in lawmaking can be understood as important input or suggestions to ensure the validity and relevance of legal products. The idea of meaningful participation emphasizes the importance of the community's role in the law-making process, especially in the formation of ideal local regulations (Perda) to support the implementation of regional autonomy. This research aims to examine the application and implications of meaningful participation in the formation of ideal local regulations, using a juridical-normative approach through three approaches: 1) statutory approach, by examining relevant regulations; 2) conceptual approach, by examining the values contained in the underlying legal concepts. This research uses primary, secondary, and tertiary legal materials to produce an ideal local regulation model in the implementation of regional autonomy. The results show that meaningful community participation is a crucial element in creating local policies that are inclusive, transparent, and responsive to community needs. The process of local regulation formation must substantially involve the community, expand public participation mechanisms, and increase transparency and the role of the legislature. Thus, meaningful participation will strengthen the legal and social legitimacy of regulations, and support the creation of democratic and accountable regional autonomy. The formation of ideal local regulations not only ensures the achievement of effective and transparent governance, but also strengthens public trust in local governments. Public participation is not just a procedure, but must be understood as the core of democracy that emphasizes the right of the people to be heard, considered, and explained for the decisions taken.